2010
DOI: 10.1007/s11926-010-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Factors and Bone Health: Effects of Weightlessness and Neurologic Injury

Abstract: Bone is a dynamic tissue with homeostasis governed by many factors. Among them, mechanical stimuli appear to be particularly critical for bone structure and strength. With removal of mechanical stimuli, a profound bone loss occurs, as best observed in the extreme examples following exposure to space flight or neurologic impairment. This review provides an overview of the changes in bone density and structure that occur during and after space flight as well as following neurologic injury from stroke and spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…9 As evidence, the reduced musculoskeletal loads after disuse result in a rapid and dramatic reduction in BMD. 10,11 Conversely, physical activity reduces osteoporotic fracture risk in older adults, 34 and load-bearing exercise improves BMD in young individuals 9 and older women receiving HT. 24,25,35 However, several meta-analyses have reported that both premenopausal 36,37 and postmenopausal 20<23 women experience very little, if any, elevation in BMD after exercise interventions, suggesting that estrogen status influences mechanical loadingYinduced bone proliferation, as has been demonstrated in vitro 38 and in vivo in various animal models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 As evidence, the reduced musculoskeletal loads after disuse result in a rapid and dramatic reduction in BMD. 10,11 Conversely, physical activity reduces osteoporotic fracture risk in older adults, 34 and load-bearing exercise improves BMD in young individuals 9 and older women receiving HT. 24,25,35 However, several meta-analyses have reported that both premenopausal 36,37 and postmenopausal 20<23 women experience very little, if any, elevation in BMD after exercise interventions, suggesting that estrogen status influences mechanical loadingYinduced bone proliferation, as has been demonstrated in vitro 38 and in vivo in various animal models.…”
Section: Discussionmentioning
confidence: 99%
“…9 For example, musculoskeletal disuse caused by space flight or neurologic insult results in a dramatic loss of BMD in humans. 10 Similarly, both cast immobilization and extended bed rest also induce rapid reductions in BMD that is of clinical concern. 11 Conversely, mechanical reloading reverses this loss and, when performed at a sufficient intensity, may further augment BMD.…”
mentioning
confidence: 99%
“…Spaceflight caused bone density reduction specifically involves weight-bearing bones (Mack et al, 1967;Vose et al, 1974;Schneider et al, 1995;Lang et al, 2006;Keyak et al, 2009). In the space environment, bone density in the lower extremities and spine of crew member is lost at a rate of 1% to 2% per month (LeBlanc et al, 2007;Amin, 2010). Microgravity disturbs the balance between bone formation and resorption in bone remolding process: it tends to increase bone resorption functions of osteoclast and decrease bone formation functions of osteoblast.…”
Section: Microarray Analysis Of Microgravity Exposed Bone Cellsmentioning
confidence: 99%
“…P2X 7 antagonists are not the only method being used in clinical trials to target P2X 7 activity, e.g., studies in the Netherlands are currently underway to determine the effect of mechanical stimulation of bone using a Juvent 1000 vibration platform in order to promote ATP release in vivo (70). Mechanical stimuli are important for maintaining normal bone structure, and ATP is released from bone cells upon mechanical stress and contributes to bone remodeling by binding to P2 receptors (2, 74). Thus, increasing mechanical stimulation and activating P2 receptors may be a novel therapeutic target for the treatment of skeletal disorders such as osteoporosis.…”
Section: P2x7 As a Potential Therapeutic Target And Biomarkermentioning
confidence: 99%